2006
DOI: 10.3354/meps315259
|View full text |Cite
|
Sign up to set email alerts
|

Food habits, selectivity, and foraging modes of the school shark Galeorhinus galeus

Abstract: The foraging ecology of the school shark Galeorhinus galeus was studied in Anegada Bay, Argentina, during the seasonal occurrence of this species in Argentinean waters (October to April) from 1998 to 2001. Of the 408 individuals examined, 168 (41.2%) had food remains in their stomachs. The proportion of individuals with food remains was negatively correlated with total length. In general, the diet was composed mainly of teleosts (98.5% IRI [index of relative importance]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
52
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 38 publications
6
52
1
Order By: Relevance
“…Previous studies comparing shark diets and prey availability estimates have shown that, during times of high prey abundance, some species (e.g. school shark Galeorhinus galeus and angel shark Squatina dumeril) can be selective predators (Lucifora et al 2006, Baremore et al 2008.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies comparing shark diets and prey availability estimates have shown that, during times of high prey abundance, some species (e.g. school shark Galeorhinus galeus and angel shark Squatina dumeril) can be selective predators (Lucifora et al 2006, Baremore et al 2008.…”
Section: Discussionmentioning
confidence: 99%
“…Birds can also use different strategies during different stages of the chick-rearing cycle (Deagle et al 2008). Adaptability in foraging strategy is also evident in other marine organisms, such as sharks (Lucifora et al 2006, Baremore et al 2008) and marine mammals (Boyd et al 1994, Skern-Mauritzen et al 2009, Arnould et al 2011. If diverse marine ecosystems such as the northern California Current are undergoing a gradual shift in the prey base, it will be crucial to monitor not only the population levels of predators in the system, but also the ability of predators to buffer those changes through behavioral flexibility.…”
Section: Discussionmentioning
confidence: 99%
“…Large-sized sharks are particularly jeopardized due to their slow life history, low densities and large home ranges (Compagno, 1990;Cortés, 2000;Frisk et al, 2001;Hutchings et al, 2012). On the Argentinean coast, the group of large-sized sharks targeted by sport and artisanal fishermen comprises: the sand-tiger shark Carcharias taurus Rafinesque, the copper shark Carcharhinus brachyurus (Günther) and the broadnose sevengill shark Notorynchus cepedianus (Péron) (Lucifora, 2003;Cedrola et al, 2011). These species are under intense sport and artisanal fishing since the 50's decade along all its range of distribution in Argentina, Uruguay and Brazil (Chiaramonte, 1998;Cedrola et al, 2011).…”
Section: Introductionmentioning
confidence: 99%